I have two difficulties on understanding the solution to an example in a course I took this semester on optimization. This example is given to illustrate the usage of Lagrange multiplier method (please see Example 1 in the image below: enter image description here

$${\Large ?}\;\left\{\begin{align*}(x_1-x_2)(x_2-x_3)(x_3-x_1)&=0\\x_1^2+x_2^2+x_3^2&=4\\x_1+x_2+x_3&=1\end{align*}\right.$$ One solution is $$x_1=x_2,\;x_3=1-2x_1,\;2x_1^2+(1-2x_1)^2=4 \\ \left(\dfrac13+\dfrac{\sqrt{22}}6,\;\dfrac13+\dfrac{\sqrt{22}}6,\;\dfrac13-\dfrac{\sqrt{22}}3\right) \\ \left(\dfrac13-\dfrac{\sqrt{22}}6,\;\dfrac13-\dfrac{\sqrt{22}}6,\;\dfrac13+\dfrac{\sqrt{22}}3\right)$$ and permutations of these.

$\underline{\text{Example 2}:}$

$$\begin{array}{ll}\text{minimize}&ax\\\text{subject to}&x_1x_2+x_1x_3+x_2x_3=0\\&x_1^2+x_2^2+x_3^2=1\end{array}$$ Necessary conditions for optimality: $$\eqalign{&{\Large\Rightarrow}\;\;\;\left\{\begin{array}{l}a_1+\lambda_1(x_2+x_3)+2\lambda_2x_1=0\\a_2+\lambda_1(x_3+x_1)+2\lambda_2x_2=0\\a_3+\lambda_1(x_1+x_2)+2\lambda_2x_3=0\\x_1x_2+x_1x_3+x_2x_3=0\\x_1^2+x_2^2+_3^2=1\end{array}\right.\\ &{\Large\Rightarrow}\;\;\;\left|\begin{matrix}a_1 & x_2+x_3 & x_1 \\ a_2 & x_3+x_1 & x_2 \\ a_3 & x_1+x_2 & x_3\end{matrix}\right|=0\\ &{\Large\Rightarrow}\;\;\;\underbrace{(x_1+x_2+x_3)}_{\neq0}\left|\begin{matrix}a_1 & 1 & x_1 \\ a_2 & 1 & x_2 \\ a_3 & 1 & x_3\end{matrix}\right|=0.}$$

I marked my question with a red "?" in the image. I can not understand how these two steps comes out. Could you please help me?

I also have the same difficulty for the second example, I hope, after I solve the first example with your help, I can understand the second one myself. But if I still fail to understand it, I'll post it and ask for help here. Sorry for my dullness in math and thank you for any help.


This is a little tricky. Notice that the system of equations:


can be rewritten as the matrix equation


Now, it follows that the $3\times 3$ matrix has a nontrivial kernel, so it cannot be invertible. Thus its determinant is $0$. If you calculate its determinant, you'll find it is $6(x_1-x_2)(x_2-x_3)(x_1-x_3)$.

  • $\begingroup$ I see. Thank you very much! $\endgroup$ – user76300 May 8 '13 at 1:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.